2013
DOI: 10.1177/0961203313486950
|View full text |Cite
|
Sign up to set email alerts
|

Systemic lupus erythematosus due to C1q deficiency with progressive encephalopathy, intracranial calcification and acquired moyamoya cerebral vasculopathy

Abstract: We report a female with infantile onset of systemic lupus erythematosus secondary to C1q deficiency, in whom we identified a novel homozygous mutation in C1qB. The patient developed a progressive encephalopathy associated with spasticity, and suffered several arterial ischaemic strokes. Cerebral imaging demonstrated acquired intracranial calcification and a cerebral vasculopathy reminiscent of moyamoya. This case demonstrates overlap with some features of Aicardi-Goutières syndrome which, like C1q deficiency, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 11 publications
1
17
0
Order By: Relevance
“…These data complement the longstanding observation of a high risk of SLE among individuals with deficiencies in early components of the complement pathway – C1q, C2 and C4 (52). While those mediators have broad functions in host defense, among their important roles is promoting clearance of debris derived from apoptotic or necrotic cells that might otherwise provide an inappropriate innate immune stimulus.…”
Section: Genetic Contributions To Activation Of the Type I Ifn Pathwaysupporting
confidence: 85%
“…These data complement the longstanding observation of a high risk of SLE among individuals with deficiencies in early components of the complement pathway – C1q, C2 and C4 (52). While those mediators have broad functions in host defense, among their important roles is promoting clearance of debris derived from apoptotic or necrotic cells that might otherwise provide an inappropriate innate immune stimulus.…”
Section: Genetic Contributions To Activation Of the Type I Ifn Pathwaysupporting
confidence: 85%
“…A link between AGS and lupus is further highlighted by the finding of highly penetrant TREX1 variants in both adults 72 and children 73 with non-syndromic SLE. Furthermore, we note that a deficiency of early complement components is associated with a high risk of childhood lupus and intracerebral vasculopathy (which is reminiscent of AGS) 74,75 , and that two studies have shown that complement protein C1q inhibits the production of IFNα by plasmacytoid dendritic cells in response to RNA-associated immune complexes and CpG DNA 76,77 ; these results possibly implicate C1q deficiency as another type of Mendelian type I interferonopathy.…”
Section: Other Type I Interferonopathiesmentioning
confidence: 94%
“…Additionally, neurological features highly reminiscent of AGS have been described in this context [39]. Two studies have shown that C1q inhibits pDC interferon alpha production in response to RNA-associated immune complexes (ICs) and CpG [40,41], possibly implicating C1q deficiency as another Mendelian type I interferonopathy.…”
Section: Sting Associated Vasculopathy With Onset In Infancy (Savi)mentioning
confidence: 98%